REKAYASA NILAI STRUKTUR DINDING PENAHAN TANAH PADA PROYEK PENANGANAN LONGSORAN JALAN PESUT KECAMATAN TENGGARONG - Dimas Wahyu Novianto; Eswan, Eswan; Hence Michael Wuaten (Media Bina Ilmiah, 2025)
The landslide mitigation project on Jalan Pesut, located in Tenggarong District, Kutai Kartanegara Regency, faces challenges in selecting an optimal technical solution that balances cost, quality, and structural functionality. This study aims to apply the Value Engineering method to evaluate alternative designs for the retaining wall structure, specifically comparing the Cantilever Retaining Wall and the Steel Sheet Pile (SSP) Wall. The research process was conducted systematically through stages of project and technical data collection, functional analysis, alternative design evaluation based on technical and cost criteria, and the formulation of recommendations. The analysis results show that the use of the Steel Sheet Pile (SSP) offers significant advantages over the Cantilever Retaining Wall, particularly in terms of cost efficiency and construction speed. The proposed budget for the Steel Sheet Pile alternative amounted to Rp 10,502,645,743.75, achieving a cost saving of up to 52% compared to the initial design. Furthermore, the use of the Steel Sheet Pile still meets technical and functional requirements in accordance with SNI 8460:2017 regarding Geotechnical Design Requirements. These findings indicate that the application of Value Engineering is highly effective in enhancing project efficiency without compromising the quality and safety of the structure. Therefore, it is recommended that this method be more widely applied to large-scale construction projects, especially those involving significant investment values and high technical risks.